Role of intraoperative transesophageal echocardiography in pediatric cardiac surgery - Jijeh, Abdulraouf M.Z. (J Saudi Heart Assoc, 2016)
BACKGROUND: Intraoperative transesophageal echocardiography (TEE) has a major role in detecting residual lesions during and/or after pediatric cardiac surgery. METHODS: All pediatric patients who underwent cardiac surgery between July 2001 and December 2008 were reviewed. The records of surgical procedure, intraoperative TEE, and predischarge transthoracic echocardiograms were reviewed to determine minor and major residual cardiac lesions after surgical repair. RESULTS: During the study period, a total of 2268 pediatric cardiac patients were operated in our center. Mean age was 21 months (from 1 day to 14 years). Of these patients, 1016 (48%) had preoperative TEE and 1036 (46%) were evaluated by intraoperative echocardiography (TEE or epicardial study). We identified variations between TEE and preoperative transthoracic echocardiography in 14 patients (1.3%). Only one surgical procedure was cancelled after atrial septal defect exclusion. The other 13 patients had minor variation from their surgical plan. Major residual lesions requiring surgical revision were detected in 41 patients (3.9%), with the following primary diagnoses: tetralogy of Fallot in 12 patients (29%), atrioventricular septal defect in seven patients (17%), ventricular septal defect in seven patients (17%), double outlet right ventricle in two patients (5%), Shone complex in two patients (5%), subaortic stenosis in two patients (5%), mitral regurgitation in two patients (5%), pulmonary atresia in two patients (5%), and five patients (12%) with other diagnoses. CONCLUSION: Intraoperative TEE has a major impact in pediatric cardiac surgery to detect significant residual lesions. Preoperative TEE has a limited role in case of a high quality preoperative transthoracic echocardiography. We recommend routine use of intraoperative TEE during and/or after intracardiac repair in children.